2012
DOI: 10.1016/j.ijsolstr.2012.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Meso-scale modelling of the size effect on the fracture process zone of concrete

Abstract: The size effect on the fracture process zone in notched and unnotched three point bending tests of concrete beams is analysed by a meso-scale approach. Concrete is modelled at the meso-scale as stiff aggregates embedded in a soft matrix separated by weak interfaces.The mechanical response of the three phases is modelled by a discrete lattice approach.The model parameters were chosen so that the global model response in the form of loadcrack mouth opening displacement curves were in agreement with experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(113 citation statements)
references
References 27 publications
3
108
0
Order By: Relevance
“…The results revealed that the length of the fracture process zone is not a material parameter as it is greatly influenced by the fracture ligament length. A meso-scale approach was used by Grassl et al [4] to investigate the effect of specimen size on the fracture process zone of concrete beams. Their study concluded that the width of the fracture process zone for notched specimens does not depend on the specimen size.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the length of the fracture process zone is not a material parameter as it is greatly influenced by the fracture ligament length. A meso-scale approach was used by Grassl et al [4] to investigate the effect of specimen size on the fracture process zone of concrete beams. Their study concluded that the width of the fracture process zone for notched specimens does not depend on the specimen size.…”
Section: Introductionmentioning
confidence: 99%
“…The system (45) writes now This choice is motivated by a damage distribution obtained from non-local damage and fracture equivalence [18], damage profiles obtained by lattice model simulations [24] and their similarity with some acoustic emission profiles [25,26].…”
Section: A Choice Of Tls Damage Profile D(φ)mentioning
confidence: 99%
“…Nazari and Riahi [71], Zhu et al [72,73] and Xu et al [74] studied the influence of inclusion and imperfect interface on the material macroscopic behavior, which explains the brittle fracture and shear dilatancy of concrete better, and plays a positive role in research of concrete local damage. Mungule [75] and Grassl [76] explored the microscopic structure of concrete containing the interfaces between aggregate and mortar, and presented the influence on the macroscopic property and the fracture process zone (FPZ). In [77], with meso-mechanics method, Wu analyzed the cracking process from microcrack initiation to macroscopic fracture in concrete dam, and evaluated the effect of different location and depth of crack on the dam safety, which were compared with lab model tests.…”
Section: The Damage Mechanism Of Dam Concrete and Foundation Rockmentioning
confidence: 99%